Directional Plk1 inhibition-driven cell cycle interruption using amphiphilic thin-coated peptide-lanthanide upconversion nanomaterials as in vivo tumor suppressors1. Issue 13 (7th April 2015) - Chan, Chi-Fai; Lan, Rongfeng; Tsang, Ming-Kiu; Zhou, Di; Lear, Sam; Chan, Wai-Lun; Cobb, Steven L.; Wong, Wai-Kwok; Hao, Jianhua; Wong, Wing-Tak; Wong, Ka-Leung
<x xml:space="preserve">Abstract</x> Polo-like kinase 1 (Plk1) is a major serine/threonine protein kinase which regulates key mitotic events.